Hubungan Status Gizi Pasien Penyakit Hirschsprung dengan Infeksi Luka Operasi di RSPAL dr. Ramelan Surabaya Periode Waktu 2016-2020 - PUTU SITHA AISHWARYA SARASWATI GIUR Giur; SAPTA PRIHARTONO RACHMAN; DIAH PURWANINGSARI; PRAWESTY DIAH UTAMI (Universitas Hang Tuah, 2022)
Background: Hirschsprung's disease is a congenital intestinal motility disorder that causes functional intestinal obstruction due to the absence of enteric ganglion cells in the distal intestine. The management of each case of Hirschsprung's disease is surgery, where surgery on the digestive tract increases the occurrence of surgical site infections. Disturbances in the gut cause decreased resistance to infection, delayed cognitive development, and problems with nutritional status. Methods: This study was a descriptive and analytical observational study, where the primary data were taken from the registration data of Hirschprung's disease patients at RSPAL dr. Ramelan Surabaya in 2016-2020. The nutritional status of the patient was determined by plotting the weight per age curve according to WHO for children aged 0-5 years. Results: Observations of 38 patients who met the study requirements, obtained 4 patients who had poor nutritional status and 1 patient who had excess nutritional status, none of which experienced complications in the form of surgical wound infections. In 10 patients with poor nutritional status, 2 experienced complications in the form of surgical wound infection and 23 patients with good nutritional status, 1 experienced complications in the form of surgical wound infection. The results of the contingency coefficient correlation test showed P-value = 0.408 (p>α). Conclusion: There was no relationship between the nutritional status of Hirschprung's disease patients with surgical wound infections at RSPAL dr. Ramelan Surabaya Keywords: Hirschsprung's disease, nutritional status of children, surgical site infection.